A transdisciplinary approach for the development of sustainable yam (Dioscorea sp.) production in west Africa - Kiba, D.I.; Hgaza, V.K.; Aighewi, B.; Aké, S.; Barjolle, D.; Bernet, T.; Diby, L.N.; Ilbondo, L.J.; Nicolay, G.; Oka, E.; Ouattara, Y.F.; Pouya, N.; et al. (MDPI, 2020)
Yam (Dioscorea sp.) is an understudied tuber crop despite its importance for food security, income generation, culture, and health in West Africa. Traditional yam cropping practices in West Africa deliver low yields and lead to environmental degradation. In the context of a ‘research for development’ project, we developed and implemented a participatory and transdisciplinary research approach as a means to derive more sustainable yam production practices. We identified and studied different soil and plant management technologies adapted to varying biophysical and socio-economic contexts. For this purpose, we established innovation platforms (IPs) in four yam growing regions of West Africa, to validate the new technologies and to promote their adoption. These co-developed technologies were set up and tested first in researcher-managed plots before doing the same in farmer-managed plots. The new technologies resulted in a significant increase in yam productivity compared to conventional practices. The results discussed in the IPs gained interest from regional stakeholders and were shared through the media at local and national levels. Overall, this development-focused research approach showcases the relevance of purposeful stakeholder involvement to improve agricultural research outcomes.